Geographies of Sexualities in Brazil: Between National Invisibility and Subordinate Inclusion in Postcolonial Networks of Knowledge Production. Issue 10 (October 2014) - Silva, Joseli Maria; Vieira, Paulo Jorge
Abstract This article reviews and examines the production of literature on sexualities in Brazilian geography, through mapping and analysing the key authors, main topics and conceptual networks. The analysis considered all the articles published on sexualities (34 articles) in Brazilian geography from 1995 to 2012, combining a review of critical concepts and a methodology of social network analysis. The study shows there was an expansion in research on sexualities in Brazil, especially in the 2000s, with a particular emphasis on concepts of territoriality and the experience of travesti. This expansion coincided with the internationalisation of scientific production in Brazil and the achievements of the Brazilian LGBT rights movement. However, despite this increase, the article explores how scientific literature on sexualities in Brazilian geography appears to be concentrated in ghettos within Brazil and, on the international scale, how it is connected in a subordinate manner to networks that are formed by the coloniality of knowledge.